2021
DOI: 10.7717/peerj.11276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pro-apoptotic potential of taxifolin against liver cancer

Abstract: Liver cancer is the second most common cause of cancer-induced deaths worldwide. Liver cirrhosis and cancer are a consequence of the abnormal angio-architecture formation of liver and formation of new blood vessels. This angiogenesis is driven by overexpression of hypoxia-inducible factor 1-alpha (Hif1-α) and vascular endothelial growth factor (VEGF). Apart from this, protein kinase B (Akt) is also impaired in liver cancer. Despite the advancement in conventional treatments, liver cancer remains largely incura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…In vitro experiments showed that treatment with taxifolin could induce apoptosis in HepG2 and Huh7 cell lines. The potential of taxifolin in the treatment of liver cancer has been confirmed, but further verification in animal model experiments is still required ( Butt et al, 2021 ).…”
Section: Therapeutic Effects Of Taxifolinmentioning
confidence: 99%
“…In vitro experiments showed that treatment with taxifolin could induce apoptosis in HepG2 and Huh7 cell lines. The potential of taxifolin in the treatment of liver cancer has been confirmed, but further verification in animal model experiments is still required ( Butt et al, 2021 ).…”
Section: Therapeutic Effects Of Taxifolinmentioning
confidence: 99%
“…Docking studies showed that the hydroxyl group of taxifolin ( 14) interacts specifically with amino acids from the binding pocket of VEGF, Akt and Hif1α which are upregulated in hepatic cancer cells. The cytotoxic potential of taxifolin ( 14) was proven by the low IC 50 values in HepG2 (0.15 µM) and Huh7 cells (0.22 µM) [80].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Pharmaceuticals 2021, 14, x FOR PEER REVIEW 9 of 32 are upregulated in hepatic cancer cells. The cytotoxic potential of taxifolin ( 14) was proven by the low IC50 values in HepG2 (0.15 µM) and Huh7 cells (0.22 µM) [80]. Silibinin or silybin is the major bioactive compound isolated from the milk thistle (Silybum marianum) extract, commonly used in the Mediterranean diet.…”
Section: Flavonoidsmentioning
confidence: 99%
“…However, rising rate of cancer drug resistance has jeopardized the chemotherapeutic treatment efficacy. Therefore, efforts are being made in identifying unique molecular targets for improving diagnosis (Khan et al., 2022 ; Khan, Safi, et al., 2020 ; Shabbir et al., 2022 ), using natural compounds as chemopreventive agents, or novel therapeutic compounds for cancer management (Butt et al., 2021 ; Khan, Quispe, et al., 2020 ; Shabbir et al., 2021 ). In this regard, an ent‐kaurane diterpenoid, ORI, first isolated from the leaves of Rabdosia rubescens may serve as a lead candidate.…”
Section: Introductionmentioning
confidence: 99%